Income inequality and mitigation burdens: An examination of climate mitigation fair shares for South African households - Reeler, James (Department of Environmental and Geographical Science, 2021)
Equity is an essential issue for climate change mitigation, especially when considering the needs of a large global population in the developing world. The principle of common but differentiated responsibilities and respective capabilities (CBDR/RC) aims to ensure equitable sharing of the climate action burden for signatories given nations' differing historical and current circumstances, but equitable burden-sharing might also be achieved if implemented through policies at a national level. South Africa is highly unequal and effectively has two parallel economies, a developed one that primarily serves the wealthy, and a developing one in which the majority of the population lives (Mbeki, 2003). As such, it internally reflects the global tension between necessary climate action and essential developmental goals. This study evaluates fair intra-national household mitigation shares in South Africa considering the principle of CBDR/RC, and the policy implications of achieving equitable mitigation action. Emulating a study by Arndt et al (2013), an energy-integrated supply-use table (SUT) model is used to examine embodied emissions for aggregate products and industries in the South African economy for three time periods (2005, 2010 and 2015). Household emissions from direct and indirect fossil fuel consumption are assessed by integrating household consumption survey data through multiplier analysis. Household emissions reflect the same “two economies” disparity as income when measured by means of both Gini and Palma indices. A small decline in inequality is observed over the study period, but overall emissions and income inequality in 2015 remain high. Grouping households by mean per capita income and expenditure, household responsibility and capability are assessed as shares of total household emissions and income, respectively. Holz et al. (2017) propose a minimal developmental threshold of $7,500 PPP below which individuals should not bear any mitigation burden, and application of this threshold provides household threshold capability and a combined mitigation and responsibility household equity estimate. Simple equity measures indicate that the top household decile's fair share of all mitigation action is between 44% and 54%, whilst the share of the bottom four deciles is between 5% and 11%. When considering the development threshold, some three-quarters of households would have no burden at all. Finally, the combined equity estimate highlights that the top decile is overwhelmingly responsible for the burden of mitigation action, with the top 2% of households by income carrying 48.1% of the mitigation burden. An assessment of the correspondence between in South Africa's international and national policy concludes that intra-national mitigation equity is necessary to achieve developmental and mitigation goals. National mitigation implementation should therefore secure revenue for mitigation through progressive means. Direct revenue recycling may enhance the security net for low-income households and provide a safety net as the country experiences unavoidable employment shifts during the transition to a low-carbon economy.